2020
DOI: 10.1007/s10068-020-00818-3
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary concepts in the functional biotics arena: a mini-review

Abstract: Over the years, the attempts to elucidate the role of beneficial microorganisms in shaping human health are becoming fairly apparent. The functional impact conferred by such microbes is not only transmitted by viable cells or their metabolites but also through non-viable cells. Extensive research to unveil the protective action of such wonder bugs has resulted in categorizing the beneficial microflora and their bioactive metabolites into a variety of functional biotic concepts based on their intended applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 87 publications
(104 reference statements)
0
13
0
7
Order By: Relevance
“…Synbiotics are a combination of both probiotics and prebiotics that induce synergistic health benefits where prebiotics are supposed to enhance the proliferation of the probiotics so they can maximally change the microbiome 123 . However, the scores for the meta‐evidence and success rate for synbiotics were not better but rather similar to probiotics and less meta‐analyses were retrieved.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Synbiotics are a combination of both probiotics and prebiotics that induce synergistic health benefits where prebiotics are supposed to enhance the proliferation of the probiotics so they can maximally change the microbiome 123 . However, the scores for the meta‐evidence and success rate for synbiotics were not better but rather similar to probiotics and less meta‐analyses were retrieved.…”
Section: Discussionmentioning
confidence: 99%
“…112 These bacteria are not yet well examined in humans but seem promising in animal studies; for example, Roseburia intestinalis decreased inflammation and restored the gut barrier 122 and are considered as next generation probiotics or led to the development of postbiotics. 123 Within the Archaea domain, the methane producing Methanobrevibacter had lower abundance in obesity and its main species Methanobrevibacter smithii showed a similar trend although some studies also found the opposite direction. There is still a lot of F I G U R E 2 Potential mechanisms between gut microbiota and metabolic health.…”
Section: Observational Reviewsmentioning
confidence: 98%
See 3 more Smart Citations